Strengthening Business Management and Simple Accounting Understanding for the Rengginang Simanalagi UMKM in Jambuluwuk Village, Ciawi District - Agni Arifah; Dea Mardianih; Gina Muzdalifah; Mia Maulani Agustin; Muhammad Hafiz Pratama; Muhamad Rosadi; Siti Amelia; Siti Anggraeni; Siti Syariafah; Prawira Yurizal; Ria Aprianti Suparna (PT FORMOSA CENDEKIA GLOBAL, 2022)
Business partners in this program are micro, small and medium enterprises (UMKM) Rengginang, which manufactures dry food products, named Rengginang Simanalagi, in Jambuluwuk village, Ciawi, Bogor. The problems faced by MSME Rengginang Simanalagi are the lack of knowledge of MSME owners about the importance of product marketing through branding and the use of technology, not doing proper financial administration so that MSMEs have difficulty determining the selling price and calculating the profits. Based on the problems above, this program will conduct training on simple accounting understanding which aims to calculate the cost of production in order to determine the selling price. then provide direction to MSME owners regarding appropriate marketing or product promotion activities so that they can attract consumer interest. The direction of this marketing activity is expected to increase product sales and introduce Rengginang Simanalagi MSME products to the wider community in order to get a bigger market potential, and is expected to be able to provide good prospects for increasing product sales figures.